Bilateral osteochondrosis of the distal tibial epiphysis. Issue 2 (March 2015) - Turati, Marco; Afonso, David; Salazard, Bruno; Maillet Declerck, Marie; Bigoni, Marco; Glard, Yann
<x xml:space="preserve">Abstract</x> Osteochondrosis is a developmental disease characterized by an alteration of endochondral ossification. Genetic causes, repetitive mechanical stresses, vascular abnormalities, hormonal imbalances, and interruption of the blood supply to the epiphyseal cartilage are all described causes of osteochondrosis and the etiology is probably multifactorial. Osteochondrosis can occur in different apophysis and epiphysis in all immature skeletons. Distal tibial epiphysis is rarely involved and most of the time unilaterally. We report on an 11-year-old female with bilateral osteochondrosis on distal tibial epiphysis. Only one other similar case has been described in the literature to date.